Long-Term Impedance Trend in Cochlear Implant Users with Genetically Determined Congenital Profound Hearing Loss. - Brotto, Davide; Caserta, Ezio; Sorrentino, Flavia; Favaretto, Niccolò; Marioni, Gino; Martini, Alessandro; Bovo, Roberto; Gheller, Flavia; Trevisi, Patrizia (Journal of the American Academy of Audiology, 2022)
Background  Impedance is a basic parameter registered at any cochlear implant (CI) fitting section. It is useful in monitoring electrode functioning and the status of the surrounding anatomical structures. Purpose  The main aim of this study is to evaluate the 5-year impedance-value trend in patients affected by congenital genetically determined profound hearing loss implanted with Cochlear Nucleus devices. Research Design  Observational, retrospective, monocentric study. Study Sample  Twenty-seven consecutive patients (9 females: 12.0 ± 7.6 years old; range: 4.2–40.4) with genetic diagnosis of GJB2 mutation causing congenital profound hearing loss who underwent cochlear implantation from 2010 to 2020 with good auditory benefit. Intervention  Impedance values of the CIs were obtained from the CIs' programming software that registers those parameters for each follow-up section of each patient. Data Collection and Analysis  Impedance values were measured over time (activation, 6, 12, 24, and 60 months after cochlear implantation), for each of the 22 electrodes, in common ground, monopolar 1, monopolar 2, and monopolar 1 + 2 stimulation modes. Results  A significant variation was found between CI activation and 6-month follow-up. This difference was found for each of the 22 electrodes. Electrodes 1 to 4 showed higher impedance values compared with all other electrodes in each time interval. Repeated-measures analysis of variance ruled out significant variations in impedance values from 6-month to 5-year follow-up. Conclusions  Impedance values were extremely stable after activation, at least for the first 5 years. In these cases, even minimal impedance variations should be carefully evaluated for their possible implications on hearing performance.